Lipid profile and lipogenic capacity of the seaweed Ulva lactuca (Chlorophyta). Use as potential ingredient for fish aquaculture . - Lopes, Íris Lameiro (2016)
LOPES, Íris Lameiro - Lipid profile and lipogenic capacity of the seaweed Ulva lactuca (Chlorophyta). Use as potential ingredient for fish aquaculture .. Coimbra : [s.n.], 2016. Dissertação de Mestrado.